STABILITAS STRUKTUR TANAH JENIS EKSPANSIF MENGGUNAKAN KOMBINASI ABU DAUN - Rekso Ajiono; Herlan Pratikto (U Karst, 2019)
In the field of land construction is a core foothold of a building. Soil structure which contains mostly clay in its components is Monmorillonite. The level of soil stability that is Montmorillonite is somewhat less good for the support of building infrastructure. The method for soil stability in the following research is to use leaf ash in addition to variations of 5%, 10%, 15%, and 20% by conducting a Water Content test and gradation test on the original soil structure used as a research sample. the beautiful town of Kediri which is Montmorillonite. The soil stability test is to use montmorillonite soil mix specimens with leaf ash by carrying out tests of Content Weight, Atterberg Limit and Proctor. The results of the original soil structure research were categorized momoroillonite and after adding coffee grounds in addition to the maximum variation of 20%, the Liquid Limit value increased to 43% and the Plastic Limit value increased to 31.64% so that the plastic index could increase to 11.36 %. When compaction test with perfect solid specimens, the original dry soil volume weight of 6.72 gr / cm3 and after adding leaf ash by 20% increased the dry volume weight to 10.56 gr / cm3.Keywords: Soil, Leaf Ash, Soil StabilityDi bidang konstruksi tanah adalah pijakan inti sebuah bangunan. Struktur tanah yang mengandung sebagian besar tanah liat dalam komponennya adalah Monmorillonit. Tingkat stabilitas tanah yaitu Montmorillonite agak kurang baik untuk mendukung pembangunan infrastruktur. Metode untuk stabilitas tanah dalam penelitian berikut adalah dengan menggunakan abu daun selain variasi 5%, 10%, 15%, dan 20% dengan melakukan tes Kadar Air dan uji gradasi pada struktur tanah asli yang digunakan sebagai sampel penelitian. . kota Kediri yang indah yaitu Montmorillonite. Uji stabilitas tanah menggunakan spesimen campuran tanah montmorillonit dengan abu daun dengan melakukan uji Berat Konten, Batas Atterberg dan Proctor. Hasil penelitian struktur tanah asli dikategorikan momoroillonit dan setelah menambahkan ampas kopi di samping variasi maksimum 20%, nilai Batas Cair meningkat menjadi 43% dan nilai Batas Plastik meningkat menjadi 31,64% sehingga indeks plastik dapat meningkat hingga 11,36%. Ketika pengujian pemadatan dengan spesimen padat sempurna, berat volume tanah kering asli 6,72 gr / cm3 dan setelah menambahkan abu daun sebesar 20% meningkatkan berat volume kering menjadi 10,56 gr / cm3.Kata Kunci: Tanah, Abu Daun, Stabilitas Tanah